1975
DOI: 10.1128/aac.8.5.574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peritoneal Dialysis on Serum Levels of Tobramycin and Clindamycin

Abstract: The pharmacokinetics of tobramycin and clindamycin were examined in patients undergoing peritoneal dialysis for chronic renal failure. Peak serum levels of tobramycin in functionally anephric patients were less than expected, probably secondary to a larger volume of distribution. Peritoneal dialysis resulted in a significant clearance of tobramycin, with a resultant reduction in serum half-life. The present data suggest that, if bactericidal serum levels of tobramycin are to be maintained in patients undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…An infected patient attained therapeutic perito neal fluid and serum levels from the intraperitoneal administration of C-PO4 during the exudative phase. The serum levels are comparable to those achieved with intra venous administration of C-PO4 [3][4][5][6], The infecting organism was not sensitive to clindamycin so his antibi otic was changed. Therefore, no evaluation was made of C-PO4 bioactivity in the postexudative phase of his infec tion.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…An infected patient attained therapeutic perito neal fluid and serum levels from the intraperitoneal administration of C-PO4 during the exudative phase. The serum levels are comparable to those achieved with intra venous administration of C-PO4 [3][4][5][6], The infecting organism was not sensitive to clindamycin so his antibi otic was changed. Therefore, no evaluation was made of C-PO4 bioactivity in the postexudative phase of his infec tion.…”
Section: Discussionsupporting
confidence: 50%
“…Malacojf et al [4] administered 600 mg of C-PO4 intravenously to 3 noninfected patients undergoing peri toneal dialysis treatments [4]. During the 1st h when the serum concentration ranged from 10 to 15 pg/ml, the mean dialysate concentration was 1.8 pg/ml.…”
Section: Discussionmentioning
confidence: 99%
“…Tobramycin removal by peritoneal dialysis has ranged in various studies from 23 to 69%o and 16.5 to 26% after intermittent and continuous ambulatory peritoneal dialysis, respectively (3,6,8,11,14,16), but was not removed by activated charcoal in our study. However, the results obtained in our normal subjects cannot be compared with those found in patients with renal failure.…”
Section: * Corresponding Authormentioning
confidence: 72%
“…The half-life of cefamandole in patient 1, calculated from antibiotic concentrations at 1, 2, 3, 4, 5, and 6 h, was 8. function (creatinine, 0.8 to 1.7 mg/100 ml; creatinine clearances, 31 to 123 ml/min), Shemonsky et al (11) observed that doses of 6 to 11 mg/kg (comparable to a dose of 500 mg) given by intramuscular injection resulted in a mean peak serum concentration of 13.7 + 3 ug/ml at 1.5 h and '1.0 ,g/ml at 6 h. In the same study, with doses in the 11-to 17-mg/kg range (approximating the 1-g intramuscular dose used in the present study), the mean peak serum concentrations were observed to be 31.0 + 17. 8 ,ug/ml at 0.5 h and 1.7 ± 0.7 u.g/ml 6 h after cefamandole administration. The calculated half-life in their study ranged from 49 to 129 min.…”
Section: Resultsmentioning
confidence: 99%